Immunomodulatory Effects of Mesenchymal Stem Cells and Mesenchymal Stem Cell-Derived Extracellular Vesicles in Rheumatoid Arthritis - Liu, Huan; Li, Ruicen; Liu, Tao; Yang, Leiyi; Yin, Geng; Xie, Qibing (Frontiers in Immunology, 2020)
Rheumatoid arthritis (RA) is a chronic autoimmune disease that affects the joints and other organs for which there is currently no effective treatment. Mesenchymal stem cells (MSCs) have therapeutic potential due to their immunomodulatory and differentiation effects. While extensive experimental studies and clinical trials have demonstrated the effects of MSCs in various diseases, MSCs have been found to cause abnormal differentiation and tumor formation. Therefore, extracellular vesicles derived from MSCs (MSC-EVs) are more effective, less toxic, and more stable than the parental cells. MSC-EVs transfer various nucleic acids, proteins, and lipids from parent cells to recipient cells, and thus participate in chronic inflammatory and immune processes. In this review, we summarize the properties and biological functions of MSCs and MSC-EVs in RA. Improvement in our understanding of the mechanisms underlying MSC and MSC-EVs in RA provides an insight into potential biomarkers and therapeutic strategies for RA.